An Evolving Paradigm of Agricultural Mechanization Development. How Much Can Africa Learn from Asia? - Diao, Xinshen; Takeshima, Hiroyuki; Zhang, Xiaobo (2021)
BOOK LAUNCH An evolving paradigm of agricultural mechanization development: How much can Africa learn from Asia? FEB 9, 2021 - 09:30 AM TO 10:30 AM EST